Değişen Eczacı Rolleri Bağlamında Hastaların Eczacılık Hizmetleri ile İlgili Memnuniyetlerinin Değerlendirilmesi - Demir, Muazez; Eke, Erdal (My University, 2020)
Eczacılık mesleğinin dönüşümü paralelinde değişen eczacı rolleri, sunulan eczacılık hizmetlerinin çeşitlenmesine ve eczacıların sorumluluklarının artmasına yol açmıştır. Sağlık sektörünün bir paydaşı olan eczacıların rollerini değerlendirme noktasında hasta memnuniyeti önemli bir parametredir. Ayrıca hasta memnuniyeti değerlendirme sonuçları, sağlık hizmetlerinin tasarım ve yönetiminde hizmet sağlayıcılara ve politika yapıcılara yol göstermede önemlidir. Bu çalışmada bireylerin eczacılık hizmetinden memnuniyetleri değerlendirilmiştir. Araştırma evrenini Isparta il merkezinde yaşayan 18 yaş üzeri bireyler oluşturmaktadır. Araştırmada kolayda örnekleme yöntemi kullanılarak 411 katılımcıya ulaşılmıştır. Araştırmada veri toplama aracı olarak, araştırmacı tarafından geliştirilen “Eczacılık Hizmetlerinin Değerlendirilmesi Anketi” kullanılmıştır. Bireylerin eczacıların danışmanlıklarından (2,928) orta derecede, eczanenin fiziki şartlarından ve eczacı ile olan iletişim boyutundan (3,929) iyi düzeyde ve ilaç kullanımı bilgilendirme boyutundan (4,092) iyi düzeyde memnun oldukları sonucuna varılmıştır. Eczacıların klasik görevlerini yerine getirdikleri ancak değişen eczacılık rollerini henüz tam olarak yerine getirmedikleri sonucuna ulaşılmıştır.

In parallel to the transformation of the pharmacy profession, the changing pharmacist roles have led to the diversification of the pharmacy services offered and the increasing responsibility of pharmacists. Patient satisfaction is an important parameter in evaluating the role of pharmacists as a stakeholder of the health sector. In addition, the results of patient satisfaction assessment are important in guiding service providers and policy makers in the design and management of health services. In this study, the satisfaction of individuals in pharmacy service was evaluated. The population of research consists of individuals over the age of 18 living in the city center of Isparta. 411 participants were reached by convenience sampling method in the study. In the study, “Pharmacy Services Evaluation Questionnaire” developed by the researcher was used as data collection tool. Individuals were partially satisfied with the counseling roles of pharmacists (2,93), they were found to be highly satisfied with the physical conditions of the pharmacist and the dimension of the contact with the pharmacy (3,93) and dimension of drug use information (4,09). Pharmacists have fulfilled their classical duties but have not yet fulfilled their changing pharmacy roles.
Evaluation of Patient Satisfaction with Pharmacy Services in The Context of Changing Pharmacist Roles